2017
DOI: 10.1212/wnl.0000000000004516
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of blood-based gene expression in idiopathic Parkinson disease

Abstract: We present a large-scale study of PD gene expression profiling. This work identifies a reliable blood-based PD signature and highlights the importance of large-scale patient cohorts in developing potential PD biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 35 publications
4
83
1
Order By: Relevance
“…Hence, there is a growing interest in detecting blood biomarkers for PD. Importantly, upregulated PTGDS was identified as being a unique blood-based signature capable of differentiating between patients with idiopathic Parkinson disease and controls in previous original studies of the microarrays [8]. A total of 1229 genes (640 up-regulated and 589 down-regulated) across the study were differentially expressed in PD with a P-value < 0.05.…”
Section: Discussionmentioning
confidence: 93%
“…Hence, there is a growing interest in detecting blood biomarkers for PD. Importantly, upregulated PTGDS was identified as being a unique blood-based signature capable of differentiating between patients with idiopathic Parkinson disease and controls in previous original studies of the microarrays [8]. A total of 1229 genes (640 up-regulated and 589 down-regulated) across the study were differentially expressed in PD with a P-value < 0.05.…”
Section: Discussionmentioning
confidence: 93%
“…We performed a similar analysis of Parkinson disease (IPD) and found no associated genes using any of the considered methods. The dataset (GSE99039 [56]) consisted of whole blood gene expression data for 205 IPD cases and 233 controls.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the change in T-cell-related pathways after exercise and its relationship with clinical measures, we hypothesized that T-cell-related functions, especially the T-cell receptor signaling pathway, were dysregulated in PD patients. To test this hypothesis, we reanalyzed publicly available microarray data (GSE99039) (22), which included peripheral blood from 205 PD patients and 233 control subjects. Genes (637 upregulated and 177 downregulated) were identified as DEGs in PD patients.…”
Section: Genes For T-cell Activation and Differentiation Were Upregulmentioning
confidence: 99%
“…In PD patients, blood-brain barrier impairment has been reported (20), and leukocytes have been identified near dopaminergic neurons in postmortem brain tissue from PD cases (21). In addition, many of the pathways implicated in neuronal dysfunction are also perturbed in peripheral blood cells from patients with PD, including altered ubiquitin-proteasome and mitochondrial pathways and the presence of alpha-synuclein peptides (22,23). In addition, evidence has suggested that peripheral inflammation plays a role in the early stages of disease initiation and progression, including the development of preclinical non-motor symptoms (19).…”
Section: Introductionmentioning
confidence: 99%